2019
DOI: 10.2215/cjn.12651018
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Zirconium Cyclosilicate among Individuals with Hyperkalemia

Abstract: Background and objectives Oral sodium zirconium cyclosilicate (formerly ZS-9) binds and removes potassium via the gastrointestinal tract. Sodium zirconium cyclosilicate-associated restoration and maintenance of normokalemia and adverse events were evaluated in a two-part, open label, phase 3 trial. Design, setting, participants, & measurements In the correction phase, adult outpatients with plasma potassium $5.1 mmol/L (i-STAT Point-of-Care) received sodium zirconium cyclosilicate 10 g three times daily for 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
135
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 142 publications
(162 citation statements)
references
References 26 publications
(33 reference statements)
9
135
0
5
Order By: Relevance
“…The findings of this study are consistent with those of previous clinical trials of SZC in patients with hyperkalaemia. [15][16][17] The Kosiborod et al study previously demonstrated significant reductions from baseline in mean serum K + of À0.7 and À1.1 mmol/L with SZC 10 g TID at 24 and 48 h, respectively, that were subsequently maintained with SZC 5, 10, or 15 g QD over 28 days. 15 Similarly, a study of 754 patients with hyperkalaemia showed significant and rapid reductions in mean central-laboratory K + levels with SZC 2.5, 5, or 10 g TID at 48 h (P < 0.001 vs. placebo for all three doses) that were maintained with SZC 5 or 10 g QD over 14 days.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The findings of this study are consistent with those of previous clinical trials of SZC in patients with hyperkalaemia. [15][16][17] The Kosiborod et al study previously demonstrated significant reductions from baseline in mean serum K + of À0.7 and À1.1 mmol/L with SZC 10 g TID at 24 and 48 h, respectively, that were subsequently maintained with SZC 5, 10, or 15 g QD over 28 days. 15 Similarly, a study of 754 patients with hyperkalaemia showed significant and rapid reductions in mean central-laboratory K + levels with SZC 2.5, 5, or 10 g TID at 48 h (P < 0.001 vs. placebo for all three doses) that were maintained with SZC 5 or 10 g QD over 14 days.…”
Section: Discussionmentioning
confidence: 98%
“…17 Of 483 patients using RAASis at baseline, 87% continued RAASi therapy or the dose was increased, and only 11% discontinued; and of 263 patients not using RAASis at baseline, 14% initiated RAASi therapy. 17,20 Thus, SZC may facilitate optimal RAASi dosing among patients with cardiovascular disease and/or CKD. In addition, maintenance of normokalaemia with SZC may reduce the need for dietary restrictions and improve patients' quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…These new drugs can link the potassium in the gastrointestinal tract, thus reducing its absorption and, as a consequence, its serum levels [15]. They have been shown to be better tolerated than sodium polystyrene sulfonate [15] and, recently, data on the efficacy of their long-term use have been also published [16]. Normokalemia was maintained for up to 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…Lokelma was well-tolerated in patients with stable CKD and hyperkalaemia [173] and in those with predialysis hyperkalaemia with end-stage renal disease undergoing adequate hemodialysis [174]. Lokelma enables substantial RAAS inhibitors to change while achieving normokalaemia [175]. However, no new evidence is available for lokelma in the field of HF.…”
Section: Hyperkalaemiamentioning
confidence: 99%
“…Omarigliptin: Gantz et al [151] AF ENGAGE AF-TIMI 48 [154], HF-ACTION [155], PARADIGM-HF/ATMOSPHERE [156], TOPCAT [157], ARISTOTLE [158], AATAC [159], CASTLE-AF [160], GENETIC-AF [163] MR MITRA-FR [165,166], COAPT [167] Hyperkalemia Patiromer: PEARL-HF [170], AMETHYST-DN [171], Patiromer-204 [172] Lokelma: Stephen et al [173], DIALIZE [174], ZS-005 [175] CSA SERVE-HF [177], Ponikowski et al [178], Pilot [179], Zhang et al [180] us to design trials to test whether a borderline EF is a signal of potential benefit from therapy targeting HFrEF and HFpEF simultaneously [186]. To date, a high-quality clinical trial specifically designed for HFpEF is still lacking, whether it is pharmacotherapy or device-based therapy.…”
Section: Treatments Key Trialsmentioning
confidence: 99%